2005
DOI: 10.1021/es050407+
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Reductive Transformation of Pentachloronitrobenzene under Methanogenic Conditions

Abstract: The reductive transformation of pentachloronitrobenzene (PCNB), an organochlorine fungicide, was investigated with a mixed, methanogenic culture developed from a contaminated estuarine sediment. Batch assays performed with this enrichment culture resulted in the biotransformation of PCNB to pentachloroaniline (PCA), which was then sequentially dechlorinated as follows: PCA --> 2,3,4,5- and 2,3,5,6-tetrachloroaniline (TeCA) --> 2,4,5- and 2,3,5-trichloroaniline (TrCA) --> 2,4-, 2,5-, and 3,5-dichloroaniline (DC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 36 publications
(38 reference statements)
2
22
0
Order By: Relevance
“…As a result, the NB reduction process was energetically replenished. This finding was similar to that of a previous study, which found that SBR performance can be quickly recovered from a threefold shock in the influent nitrophenols concentration after the addition of sufficient carbon sources .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…As a result, the NB reduction process was energetically replenished. This finding was similar to that of a previous study, which found that SBR performance can be quickly recovered from a threefold shock in the influent nitrophenols concentration after the addition of sufficient carbon sources .…”
Section: Resultssupporting
confidence: 91%
“…Previous studies have also reported that the influent NB concentrations and loading rates could influence NB removals by the applied anaerobic reactors such as ABR, AMBR, and CSTR reactors ; and that the measured IC 50 was always below 50 mg L −1 , indicating the heavy toxicity of NB under shocked influent concentration and this in turn decreased the NB removals in this study. Apart from NB reduction, a previous study also suggested that the nitro group associated compounds such as pentachloronitrobenzene (PCNB) could also inhibit the biological activities in dechlorinating pentachloroaniline (PCA) .…”
Section: Resultsmentioning
confidence: 99%
“…Total gas production was measured by displacement of an acidified brine solution (10% NaCl w/v and 2% H 2 SO 4 v/v) in graduated burets. The gas composition was determined by gas chromatography with thermal conductivity as previously reported. , …”
Section: Methodsmentioning
confidence: 99%
“…PCNB degradation intermediates viz; pentachloroaniline (PeCA), tetrachloroaniline (TeCA), trichloroaniline (TCA) and dichloroaniline (DCA) from anaerobic enriched soil sample have been identified by HPLC with the retention time 3.532, 5.375, 4.121, 6.951 min and UV-absorption spectra 246.9, 308.5, 248.1, 221.1 nm (Figure 1). There are few reports on degradation of PCNB by anaerobic mixed culture via reductive dechlorination under anaerobic condition [22,25]. Similarly, HCB degradation intermediates from anaerobic enrichment were identified as pentachlorobenzene (PeCB), tetrachlorobenzene (TeCB), trichlorobenzene (TCB) and dichlorobenzene (DCB) with the retention time 16.31, 9.746, 12.06, 4.976 min and UV-absorption spectra 287.1, 229.3, 268.2, 284.8 nm (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, there has been an increase in effort to remove PCNB, HCB and their possible intermediates from the environment either by abiological or biological means during the past decades. The biotransformation products of PCNB include pentachloroaniline (PeCA), tetrachloroaniline (TeCA), trichloroaniline (TCA), dichloroaniline (DCA), chloroaniline (CA), pentachlorophenol (PCP), pentachlorothiophenol, pentachlorothioanisole and pentachloromethyl-phenyl sulfoxide [22-25]. The biotransformation products of HCB are pentachlorobenzene (PeCB), tetrachlorobenzene (TeCB), trichlorobenzene (TCB), dichlorobenzene (DCB), pentachlorophenol (PCP), tetrachlorohydroquinone (TeCH) and dichlorohydroquinone (DiCH) [14-16].…”
Section: Introductionmentioning
confidence: 99%